Shifts in Translation of English Noun Phrases into Indonesian with Reference to the Short Story A Scandal in Bohemia - Finsen, Harvin Thedeolin; Puspani, Ida Ayu Made (Humanis; Vol 23 No 3 (2019)DO - 10.24843/JH.2019.v23.i03.p01, 2019)
Shifts in translation of English noun phrases into Indonesian with reference to a short story A Scandal in Bohemia is a study of how to transfer a message, information from one to another language to overcome its language barrier. Due to the systematical difference of every language, the occurrence of the translation shift is unavoidable in order to make the translation result natural. Translation shift and meaning equivalent are two core elements in translation that are correlated and inseparable, this study is conducted to find out the types of translation shifts and their implication towards the meaning equivalents found in the short story “A Scandal in Bohemia”. The data was taken from a short story entitled “A Scandal of Bohemia” using documentation and note-taking technique. In addition, the data was analyzed qualitatively and comparatively. It was classified based on the types of shifts and the analysis of its implication towards the meaning equivalent under the theory of Translation Shift proposed by Catford (1965) about translation shift and Theory of Meaning-Based Translation proposed by Larson (1998).This study revealed that the occurrence of the translation shift can be classified into four types of shift namely structure shift, class shift, unit shift and intra-system shift in which all of them belong to the category shift. None of the data shown level shift occurrence. This study also revelaed that as what Catford (1965) has stated in his theory that the most frequent shift is the structure shift, meanwhile the least one is the class shift. Multiple shifts are also occurred in some of the NPs, there are a few pairs namely unit and class shifts, class and intra-system shifts, unit and intra-system shifts and structure and intra-system shifts are occurred . Furthermore the implication of translation shift towards the meaning equivalent is also the core aspect in this study; it is shown that the occurrence of the shift is obligatory in order to make an equivalent and natural translation which the meaning that is carried from the SL to the TL is held constant and relevant to the feature of substance.